SISTEM LAHAN PARKIR OTOMATIS MENGGUNAKAN ESP32 BERBASIS WEB - M. KHAIRUL JIMLI ALFUADI; Habib Muharry Yusdartono; Dahlan Abdullah; Muhammad Ikhwanus; T. Iqbal Faridiansyah; Fitria Apriyulida (Smart Education, 2026)
The vehicle increase is not proper to parking availability and then high rate of public consumtion at Mall affecting to traffic jam, polution and inapropriate time wasting. Although parkir space is expanded by owner, improfessional car parking management is made of ineffective in parking space management. An instrument is required to able to automaticly watch of parking space; therefore parking space is able to be better managed. This research is aimed to design an automatic parking space to monitor a parking lot that this adopt ESP32 and Firebase. The system planned in this research employs 4 Ultrasonic sensor to detect vehicles, after that the output of sensors send data to Firebase through an WiFi connection. Infrared sensor is added to system in this research to get the best result and tilt angle of Servo to object is going to be adjusted. Ultrasonic and Infrared sensors are tested with giving a space about 1-20 cm. The servo angle is adjusted until its angles are 00, 450, 900, 1350, and 1800. Web is designed to show some parking lot items such as number of spot parking being avalailale and full, daily wages got from parking charge. Ultrasonic and Infrared sensor resut is taken when sensor range is taken in 1-19 cm. Nevertheless sensor is not detected in when sensor range is 20 cm. On the other hand, servo angle test is shown that the gate is closed in 00, gate is half open condition in 450, and fully open when the gate conditions are 900, 1350, and 1800. The use of Web is design reaching to show simultaneously parking data.